Extent of MGMT Promoter Methylation Modifies the Effect of Temozolomide on Overall Survival in Patients with Glioblastoma: A Regional Cohort Study. (1st October 2022) - Poon, Michael T C; Keni, Shivank; Vimalan, Vineeth; Ip, Chak; Smith, Colin; Erridge, Sara; Weir, Christopher; Brennan, Paul
Abstract: AIMS: MGMT methylation in glioblastoma predicts response to temozolomide but dichotomizing methylation status may mask the true prognostic value of quantitative MGMT methylation. This study evaluated whether extent of MGMT methylation interacts with the effect of temozolomide on overall survival. METHOD: We included consecutive glioblastoma patients aged ≥16 years diagnosed (April 2012–May 2020) at a neuro-oncology center. All patients had quantitative MGMT methylation measured using pyrosequencing. Those with MGMT methylated tumors were stratified into high and low methylation groups based on a cut-off using Youden index on 2-year survival. Our accelerated failure time survival models included extent of MGMT methylation, age, postoperative Karnofsky performance score, extent of resection, temozolomide regimen, and radiotherapy. RESULTS: There were 414 patients. Optimal cut-off point using Youden index was 25.9% MGMT methylation. The number of patients in the unmethylated, low and high methylation groups was 223 (53.9%), 81 (19.6%), and 110 (26.6%), respectively. In the adjusted model, high (hazard ratio [HR] 0.60, 95% confidence intervals [CI] 0.46– 0.79, P=0.005) and low (HR 0.67, 95% CI 0.50–0.89, P<0.001) methylation groups had better survival compared to unmethylated group. There was no evidence for interaction between MGMT methylation and completed temozolomide regimen (interaction term for low methylation P=0.097; high methylation P=0.071). This suggests no strong effect of MGMT status on survival in patients completing temozolomide regimen. In patients not completing the temozolomide regimen, higher MGMT methylation predicted better survival (interaction terms P<0.001). CONCLUSION: Quantitative MGMT methylation may provide additional prognostic value. This is important when assessing clinical and research therapies.